Crisis and transformation of news media organizations: the rise and fall of business models - (:unkn) unknown (My University, 2025)
This is a subproject (B) of the main project entitled "Crisis and transformation of the core media sector in Switzerland", directed by the SwissGIS Research network. The main project takes the structural crisis of the core media (dt. Leitmedien) as a starting point, to analyze and reflect in depth on the origins, forms and consequences of this crisis for the media system itself as well as for democracy and society as a whole, and to explore possible answers. The central goals of the research network are as follows: (a) A contribution to communications research and to the public debate on the crisis, challenges and transformation of the traditional core media from a six-dimensional approach on the theoretical level with an empirical focus on tri-lingual Switzerland. (b) A contribution to the current debate on the growing importance of the Internet and Web 2.0 in the context of forms of social compliance and mediation. (c) A contribution to an in-depth debate on the role of the traditional core media on the one hand, and the new online communication on the other, for the processes of political socialization and participation in the democratic society. The subproject B focuses on organizational and strategic management issues and seeked to a) find out how the management of the core media acknowledged and confronted the structural crisis; b) grasp how the new media have been incorporated into the strategic considerations of newspaper publishers and c) develop a meta model which could enable businesses to react to their changing social environment.
Keywords: business models; strategic media management; news media